2020
DOI: 10.1016/j.cattod.2019.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of glucose to 5-hydroxymethylfurfural over biomass-based activated carbon catalyst

Abstract: Highlights  Biomass-based activated carbon catalysts modified with Lewis or Brønsted acid sites were prepared  Catalysts were used to convert glucose to HMF in biphasic water:THF system  51% HMF yield was obtained with catalytic mixture containing both Lewis and Brønsted acid sites  The water phase containing the catalyst was recycled successfully Abstract Selective and efficient dehydration of glucose to 5-hydroxymethylfurfural (HMF) has been widely explored research problem recently, especially from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 65 publications
1
26
0
1
Order By: Relevance
“…From 2nd to 3rd run, conversion reduced from 57.2 to 38.3%, while the 5-HMF selectivity has stabilized. This behavior is similar to that previously observed (Nunes et al, 2020) and also reported in other works (Portillo Perez et al, 2019;Rusanen et al, 2019). The main reasons found in the literature are (I) loss of -COOH/-SO3H groups and (II) deactivation of the acid sites by deposition/anchoring of humins on carbon surface.…”
Section: Catalytic Testssupporting
confidence: 92%
“…From 2nd to 3rd run, conversion reduced from 57.2 to 38.3%, while the 5-HMF selectivity has stabilized. This behavior is similar to that previously observed (Nunes et al, 2020) and also reported in other works (Portillo Perez et al, 2019;Rusanen et al, 2019). The main reasons found in the literature are (I) loss of -COOH/-SO3H groups and (II) deactivation of the acid sites by deposition/anchoring of humins on carbon surface.…”
Section: Catalytic Testssupporting
confidence: 92%
“…The process to convert glucose into HMF is influenced by several variables, such as the temperature, type of catalyst, reaction time, and reaction medium composition. Regarding the reaction medium, a variety of solvents has been evaluated for such a purpose, including aqueous, organic, and biphasic systems (water mixtures and organic solvents), as well as ionic liquids [8][9][10][11]. Glucose dehydration reactions tend to be more selective in the presence of aprotic solvents, e.g., dimethylsulfoxide (DMSO), tetrahydrofuran, acetone, and n-butanol.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 94 productso btained from these sugars, 25 were selected as involving feasible technologiest hat are suitablef or large-scale prototype testing in ap ilot plant. [11][12][13] Other research has focused on optimizingh eterogeneous catalysts for dehydration reactions involving both metal catalysts [14][15][16][17][18][19][20] and supported ionic liquids. [3] The main route to form HMF is by the dehydration of sugars, [4] and important resultsh ave been achieved for HMF production using ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Deep eutectic solvents andw ater have also been investigated for the dehydration of fructose into HMF but improvedy ields are still needed. [11][12][13] Other research has focused on optimizingh eterogeneous catalysts for dehydration reactions involving both metal catalysts [14][15][16][17][18][19][20] and supported ionic liquids. [21,22] In particular, ionic liquidsw ith halide counteranions have provenv ery efficient for the production of HMF from fructose, glucose,a nd cellulose with both Brønsted and Lewis acid catalysts.…”
Section: Introductionmentioning
confidence: 99%